Sucrose targets clathrin-mediated endocytosis kinetics supporting cell elongation in Arabidopsis thaliana - Osorio-Navarro, Claudio; Toledo, Jorge; Norambuena, Lorena (Frontiers in Plant Science, 2022)
Sucrose is a central regulator of plant growth and development, coordinating cell division and cell elongation according to the energy status of plants. Sucrose is known to stimulate bulk endocytosis in cultured cells; however, its physiological role has not been described to date. Our work shows that sucrose supplementation induces root cell elongation and endocytosis. Sucrose targets clathrin-mediated endocytosis (CME) in epidermal cells. Its presence decreases the abundance of both the clathrin coating complex and phosphatidylinositol 4,5-biphosphate at the plasma membrane, while increasing clathrin complex abundance in intracellular spaces. Sucrose decreases the plasma membrane residence time of the clathrin complex, indicating that it controls the kinetics of endocytic vesicle formation and internalization. CME regulation by sucrose is inducible and reversible; this on/off mechanism reveals an endocytosis-mediated mechanism for sensing plant energy status and signaling root elongation. The sucrose monosaccharide fructose also induces CME, while glucose and mannitol have no effect, demonstrating the specificity of the process. Overall, our data show that sucrose can mediate CME, which demonstrates that sucrose signaling for plant growth and development is dependent on endomembrane trafficking.